1968
DOI: 10.1063/1.1652483
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Diffraction Topography With a Vidicon Television Image System

Abstract: Reproduction of x-ray diffraction topographic images has been made at about 25 diameters enlargement by a closed-circuit television camera system with an x-ray sensing Vidicon tube which utilizes a beryllium window and PbO photoconductive target. The height of video signals is exactly proportional to x-ray intensity, and intensity distribution can be observed as a video waveform. It is shown that the television image system can be used for rapid observations of topographic images such as Pendellösung fringes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

1971
1971
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 6 publications
0
20
0
1
Order By: Relevance
“…Many authors have reported systems based on X-ray sensitive vidicons (Chikawa & Fujimoto, 1968), conventional television with phosphor screens, sometimes with image intensifiers interposed (Meieran, Landre & O'Hara, 1969;Lang & Reifsnider, 1909;Kozaki, Hashizume & Kohra, 1972) and charge sensitive diode arrays (Rozgonyi, Haszko & Statile, 1970). With conventional sources these authors reported exposure times between 0.5 s and one minute with resolutions in the range from 10/~m to 30/zm over areas of a few mm square.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have reported systems based on X-ray sensitive vidicons (Chikawa & Fujimoto, 1968), conventional television with phosphor screens, sometimes with image intensifiers interposed (Meieran, Landre & O'Hara, 1969;Lang & Reifsnider, 1909;Kozaki, Hashizume & Kohra, 1972) and charge sensitive diode arrays (Rozgonyi, Haszko & Statile, 1970). With conventional sources these authors reported exposure times between 0.5 s and one minute with resolutions in the range from 10/~m to 30/zm over areas of a few mm square.…”
Section: Introductionmentioning
confidence: 99%
“…(5) If the present filter method is combined with direct observation by any of various television display systems (Chikawa & Fujimoto, 1968;Meieran, Landre & O'Hara, 1969;Chester & Koch, 1969;Lang & Reifsnider, 1969;Rozgonyi, Haszko & Statile, 1970) and with a powerful X-ray source such as already reported (Shimura, Yoshimatsu & Uematsu, 1969), the area observable at any one time may become much wider. By such a composite method, the regions can simultaneously be observed even if they are slightly misoriented with each other.…”
Section: Discussion and Commentsmentioning
confidence: 99%
“…28,31) At the 4th International Conference on Crystal Growth in Tokyo, a movie of X-ray topographic images showing growth processes of Si crystals from the melt was exhibited. 29) This type of technique was referred to as "live X-ray topography" 30) and has been used for in-situ observations of defects, crystal growth, and phase transformation.…”
Section: Methods Of Live X-ray Topographymentioning
confidence: 99%
“…29,31) In 1968, we reported on this type of X-ray imaging system that could instantaneously display individual dislocations in a BeO crystal on a TV monitor. 28) Moving dislocations in an Si crystal were observed in 1972. 39) Since then, in order to realiz such TV displays of X-ray topographs with a conventional X-ray generator, many investigators developed various types of TV cameras with very high sensitivities; 17) most of them were of the indirect type in which X-ray images are first converted into visible-light images by phosphor screens.…”
Section: Imaging Systemmentioning
confidence: 99%
See 1 more Smart Citation